- #1

- 1

- 0

[[[A,B],B]A]=[B,[A,[A,B]]]

- Thread starter S.G.
- Start date

- #1

- 1

- 0

[[[A,B],B]A]=[B,[A,[A,B]]]

- #2

- 703

- 13

you could first use the abbreviation C:= [A,B], so the equation

looks better:

[[[A,B],B]A]=[B,[A,[A,B]]]

<=>

[[C,B],A] = [B,[A,C]]

Then use the definition of the commutator [Y,Z] = YZ-ZY

and in the end, instead of C, use [A,B] again.

- Replies
- 12

- Views
- 3K

- Replies
- 1

- Views
- 725

- Replies
- 4

- Views
- 720

- Replies
- 1

- Views
- 3K

- Last Post

- Replies
- 3

- Views
- 4K

- Last Post

- Replies
- 3

- Views
- 1K

- Last Post

- Replies
- 2

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 14

- Views
- 325

- Last Post

- Replies
- 4

- Views
- 2K